Possibilities of Anxiolytic Therapy in the Elimination of Stress Skin Manifestations: A Case Report - Sydorova, Nataliia; Vereshchaka, Volodymyr; Kuts, Taras (Acta medica Lituanica, 2023)
The case of a 42-year-old female patient with pronounced itching and exanthema, mainly in the area of the trunk and lower limbs, is presented. Previously, the patient took antihistamines without effect, was treated for scabies, but the itching remained pronounced and led to rash and excoriations. From the anamnesis, it was found that the patient has a high level of stress. According to the Hospital Anxiety and Depression Scale, the anxiety of the patient reached 14 points, and depression 1 point. Functional (psychogenic) itching was suspected. Since the patient refused dermatologist consultation, therapy with the anxiolytic temgicoluril, topical antipruritic agents and nonpharmacological methods of treatment were recommended at the initial stage. The patient felt a significant relief of itching symptoms on the first day of anxiolytic usage, she withdrew topical antipruritic agents after 5 days of anxiolytic treatment, in 15 days she began to reduce the dose of temgicoluril, and at the end of the third week she stopped treatment with anxiolytic due to a significant positive effect. In three weeks, practically all elements of the rash, except for the largest wounds from scratching, disappeared. The peculiarity of the case is that functional itching was completely eliminated during anxiolytic therapy without other systemic medications, which emphasizes the importance of eliminating the component of stress and anxiety in the treatment of such patients.